Waiting for the postcolonial turn: challenging experiences in West African universities and in the field of sociology of law - Zevounou, Lionel (Oñati Socio-Legal Series, 2022)
Online unter folgendem Titel: From a French minority point of view: Perspectives on socio-legal studies in Europe